Fourfold magnetic anisotropy induced in CoFeB/IrMn bilayers by interfacial exchange coupling - Xinwei Feng; Jing Meng; Xiaoyan Zhu; Kelei Xue; Yali Xie; Dongmei Jiang; Yang Xu; Tian Shang; Yong Hu; Qingfeng Zhan (New Journal of Physics, 2023)
Exchange bias (EB) occurring in ferromagnetic (FM)/antiferromagnetic (AFM) bilayers conventionally can lead to a unidirectional magnetic anisotropy ( ${K_{{\text{eb}}}}$ ) as well as an accompanied uniaxial magnetic anisotropy ( ${K_{\text{u}}}$ ). We observed an additional fourfold magnetic anisotropy ( ${K_4}$ ) induced by interfacial exchange coupling in amorphous CoFeB/epitaxial IrMn bilayers with an EB. Because of the combined effect of the three kinds of magnetic anisotropies, one- and two-step magnetic switching processes were observed at different magnetic field orientations, which usually appear in single-crystal FM layer with an intrinsic magnetocrystalline anisotropy but not in amorphous FM layer. The angular dependent magnetic switching fields can be nicely fitted by a phenomenological model based on domain wall nucleation and propagation with the in-plane ${K_4}$ along <100>. The ferromagnetic resonance measurements indicate that the specific strength of ${K_4}$ for EB along [100] is larger than that for EB along [110]. The induced ${K_4}$ can be understood by considering two types of AFM domains caused by both monatomic steps and defects and their induced net uncompensated spins along the in-plane <100> axes. The different dependence of ${K_4}$ on the EB direction are because of the different effects of growth magnetic field on the presence of AFM domains.